The Effects of University English Writing Classes Focusing on Self and Peer Review on Learner Autonomy - Lee, Hyoshin (Journal of Asia TEFL, 2017)
The study aimed to investigate the effects of English writing classes focusing on self and peer review on learner autonomy at a Korean university, leading to finding ways to improve the quality of the English writing classes. An English writing class consisting of 29 students majoring in English language was organized and lessons were provided over a period of seven weeks. An online questionnaire was conducted to identify students' perceptions of the effects of the English writing class on motivation, responsibility, ability to make choices in learning activities, and engagement in learning activities. An open-ended questionnaire was also conducted with four students, the teacher who implemented the program, and one academic professional in L2 writing instruction. It was found that the English writing class focusing on self and peer review had positive effects on students' perception of students' and teachers' responsibilities and English learning activities outside classrooms while it had moderate effects on their motivation and English learning activities inside the classroom. Secondly, the results of the open-ended questionnaire to the students and the teachers implied that students' writing competences might improve. In addition, more systematic learner training needs to be provided to increase the effects of the class, particularly the effects of self and peer review. Finally, it was found that the clarity of the responsibility between teachers and students did not lead to the increase of the ability to choose the learning activities. Attention needs to be paid to how to increase the ability.